Anthracyclines and trastuzumab associated cardiotoxicity: is the gut microbiota a friend or foe? – a mini-review - Gonçalves-Nobre, J. Guilherme; Gaspar, Inês; Alpuim Costa, Diogo (Frontiers in Microbiomes, 2023)
Breast cancer (BC) is one of the most prevalent cancers worldwide. Fortunately, BC treatment has taken a huge turn in the last few years. Despite these advances, one of the main issues related to systemic treatment remains the management of its side effects, including cardiotoxicity. In this regard, we highlight the irreversible dose-dependent cardiotoxicity of anthracyclines related to oxidative stress and the reversible cardiotoxicity with trastuzumab, whose mechanism is still poorly understood. Moreover, the combination of anthracyclines and trastuzumab further exacerbate the myocardial damage. More recently, altered gut microbiota composition has been linked to the long-term effects of cancer therapy, including the potential connection between treatment-related microbial changes and cardiotoxicity. Bacteroides spp., Coriobacteriaceae_UGC-002, and Dubosiella have already been reported as bacterial species with deleterious effects on the myocardium, mainly due to the promotion of inflammation. On the other hand, Alloprevotella, Rickenellaceae_RC9, Raoultella planticola, Klebsiella pneumoniae, and Escherichia coli BW25113 can induce cardioprotection, predominantly by increasing anti-inflammatory cytokines, promoting intestinal barrier integrity and early metabolization of doxorubicin. Herein, we explore the role of gut microbiota in the development of cardiotoxicity, as well as future perspectives to decrease the risk of cardiotoxicity associated with BC treatment.